2.4 V All‐Manganese Aqueous Rechargeable Cell. Issue 2 (25th January 2022) - Xie, Minghao; Kong, Shuting; Su, Linghao
Abstract: We report the construction of 2.4 V aqueous manganese dioxide (MnO2 )|manganese (Mn) rechargeable cell, not needing the combination of cation and anion exchange membranes and a third electrolyte chamber. This novel designs using Mn metal as negative electrode and MnSO4 acidic solution as electrolyte, avoids the side reactions of MnO2 −Zn batteries in alkaline electrolyte and exhibits 2.1 V operating voltage and 87.8 % of MnO2 's theoretical one‐electron capacity (308 mAh/g) at C/6 rate. After charging and discharging continuously for 100 cycles at 50 % charge depth of MnO2, the capacity retention rate is still 89.2 %. Abstract : All Manganese : A MnO2 |Mn aqueous cell displays 2.4 V open‐circuit voltage, 2.1 V operating voltage at C/6 rate and a capacity retention rate of 89.2 % after 100 charge/discharge cycles at 50 % charge depth of MnO2 . Only acidic electrolytes are employed as both anolyte and catholyte without the need of anion and cation exchange membranes or a third neutral electrolyte chamber.